2022
DOI: 10.1177/0044118x211067553
|View full text |Cite
|
Sign up to set email alerts
|

Staying Online, Staying Connected: Exploring the Effect of Online Chatting on Adolescents’ Psychological Well-being during COVID-19 Quarantine

Abstract: Rooted in scholarship of social connectedness and social support, this research raises the question: Can online chatting help mitigate the negative psychological influence of physical distancing during COVID-19? By a correlational and cross-sectional research design, the current study testified the mediating role of two factors—social connectedness and perceived social support in the relationship between online chatting and three indicators of psychological well-being (happiness, self-esteem, and loneliness) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The restrictions imposed during the pandemic severely limited the options and opportunities for live social interactions. In this regard, it was found that during the pandemic online communication indeed enabled adolescents' higher levels of social connectedness and subjective well-being, including self-esteem (Ellis et al, 2020;Feng & Tong, 2022). Still, it is important to emphasize that these findings also show that despite their positive effect, online interactions cannot serve as a substitute for person to person socializing, especially in times where social gathering is possible.…”
Section: Discussionmentioning
confidence: 96%
“…The restrictions imposed during the pandemic severely limited the options and opportunities for live social interactions. In this regard, it was found that during the pandemic online communication indeed enabled adolescents' higher levels of social connectedness and subjective well-being, including self-esteem (Ellis et al, 2020;Feng & Tong, 2022). Still, it is important to emphasize that these findings also show that despite their positive effect, online interactions cannot serve as a substitute for person to person socializing, especially in times where social gathering is possible.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, our results suggest that a social-oriented use of digital technologies is an online behaviour that should be promoted to protect the well-being of young people already at an early age -particularly when other kinds of social contacts, such as contacts with peers, are not available. To sum up, we can say that online interaction is a 'supplementary perspective' (Feng & Tong, 2022) since it mitigates the detrimental effect of Covid-19 containment measures by relieving stress and getting positive feedback and support from others, thus promoting LS.…”
Section: Discussionmentioning
confidence: 99%
“…The new technologies made it possible to maintain relationships with friends, family and others, even create new ones, and were thus an important resource for dealing with the pandemic and upholding important dimensions of a good adolescence. How well this worked certainly depended on several factors, including the relationships that existed before the pandemic, the availability of these technologies, personal preferences and support from others or monitoring by parents (Foulkes and Blakemore 2021;Feng and Tong 2022). For some adolescents, therefore, the pandemic changed their lives less than it did for others, and for others the reduction in "real life" contacts was even a relief.…”
Section: Being Young In Times Of a Pandemicmentioning
confidence: 99%